Lactobacillus paracasei L9 affects disease progression in experimental autoimmune neuritis by regulating intestinal flora structure and arginine metabolism - Yuting Meng; Xiangjie Qiu; Zhongxiang Tang; Yu Mao; Yurong Tan (Journal of Neuroinflammation, 2023)
Abstract Background Autoimmune neuropathies are common peripheral nervous system (PNS) disorders. Environmental influences and dietary components are known to affect the course of autoimmune diseases. Intestinal microorganisms can be dynamically regulated through diet, and this study combines intestinal microorganisms with diseases to open up new therapeutic ideas. Methods In Lewis rats, a model of EAN was established with P0 peptide, Lactobacillus were used as treatment, serum T-cell ratio, inflammatory factors, sciatic neuropathological changes, and pathological inflammatory effects on intestinal mucosa were detected, and fecal metabolomics and 16 s microbiome analysis were performed to further explore the mechanism. Results In the EAN rat model, Lactobacillus paracasei L9 (LP) could dynamically regulate the CD4+/CD8+T balance in serum, reduce serum IL-1, IL-6 and TNF-α expression levels, improve sciatic nerve demyelination and inflammatory infiltration, and reduce nervous system score. In the rat model of EAN, intestinal mucosa was damaged. Occludin and ZO-1 were downregulated. IL-1, TNF-α and Reg3γ were upregulated. LP gavage induced intestinal mucosa recovery; occludin and ZO-1 upregulation; IL-1, TNF-α and Reg3γ downregulation. Finally, metabolomics and 16 s microbiome analysis were performed, and differential metabolites were enriched with an important metabolic pathway, arginine and proline metabolism. Conclusion LP improved EAN in rats by influencing intestinal community and the lysine and proline metabolism.